Dissolved REE concentrations in near-bottom water samples from RV Meteor cruise M147 - Antao Xu; Ed C Hathorne; Florian Scholz; Ling Chen; Andrea Koschinsky; Martin Frank (PANGAEA, 2025)
All samples were obtained during RV Meteor cruise M147 (April–May 2018), conducted as the official process study GAPR11 within the framework of the international GEOTRACES program.
In: Xu, A et al. (2025): Dissolved neodymium and hafnium isotopes and rare earth element data of near-bottom water samples from RV Meteor cruise M147 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.986565